(untitled) (International Journal of Engineering and Computer Science, 2016)
Image compression has become an important process in today’s world of information exchange. Image compression helps in effective utilization of high speed network resources. The main objective is to design a compression system suitable for processing, storage and transmission, as well as providing acceptable computational complexity suitable for practical implementation. The two compresson technique DCT and DWT are widely used. DCT is an orthogonal transform, the Discrete Cosine Transform (DCT) attempts to decorrelate the image data. After decorrelation each transform coefficient can be encoded independently without losing compression efficiency. Discrete Wavelets Transform (DWT) is a mathematical tool for changing the coordinate system in which we represent the signal to another domain that is best suited for compression. The objective of the thesis is to compare two compression techniques (DCT & DWT) and validate the results using MATLAB programming